2015
DOI: 10.1111/geb.12364
|View full text |Cite
|
Sign up to set email alerts
|

Diversity enhances carbon storage in tropical forests

Abstract: Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass (AGB) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
358
10
19

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 422 publications
(464 citation statements)
references
References 46 publications
51
358
10
19
Order By: Relevance
“…More specifically, it was found that species richness was significantly and positively correlated with AGC. Indeed, it is a well-known pattern, especially at the global scale, that carbon stocks increase with increasing diversity [27,29,65]. The positive relationships between tree species diversity and carbon stocks in this study supports the idea that diversity-carbon patterns are also identifiable even at smaller spatial scales.…”
Section: Agb and Agc Stocks At The Stand Levelsupporting
confidence: 84%
See 1 more Smart Citation
“…More specifically, it was found that species richness was significantly and positively correlated with AGC. Indeed, it is a well-known pattern, especially at the global scale, that carbon stocks increase with increasing diversity [27,29,65]. The positive relationships between tree species diversity and carbon stocks in this study supports the idea that diversity-carbon patterns are also identifiable even at smaller spatial scales.…”
Section: Agb and Agc Stocks At The Stand Levelsupporting
confidence: 84%
“…Multispecies allometric equations have extensively been studied and offer possibilities to accurately estimate forest biomass at smaller scales, and to elucidate the relationships of forest biomass with stand variables. Recent studies have shed light on the influence of forest stand variables and tree species diversity on the forest biomass and carbon stocks [25][26][27], and how these relationships can serve not only to suggest appropriate management strategies to increase carbon storage [20], but also to test niche complementarity and selection effect hypotheses [28,29]. The niche complementary hypothesis suggests that higher diversity in forest ecosystems would allow a greater variety of functional traits and provide opportunities for efficient resource utilisation, thereby increasing ecosystem functions (for example, carbon storage).…”
Section: Introductionmentioning
confidence: 99%
“…Many current silvicultural guidelines strive for more heterogeneous stands (Utschig et al 2011;Pretzsch and Zenner 2017) as they may provide many ecosystem goods and services Poorter et al 2015;Mensah et al 2016;Dieler et al 2017) better than monocultures. The finding that small trees benefit in relation to tall trees from dry years and on dry sites (see also Pretzsch and Biber 2010) means that structural heterogeneity, as aimed at by many modern silvicultural guidelines, is easier to maintain on poor dry sites.…”
Section: Silvicultural Implicationsmentioning
confidence: 99%
“…Além disso, atributos florísticos e fitossociológicos contribuem diretamente para determinação da biomassa e carbono em florestas tropicais (Poorter et al, 2015). A contribuição de cada espécie para o estoque de biomassa e carbono depende da sua abundância e também das propriedades funcionais de seus indivíduos, como seu tamanho e densidade da madeira (Fauset et al, 2015).…”
Section: Introductionunclassified